2009
DOI: 10.1007/s00520-009-0604-8
|View full text |Cite
|
Sign up to set email alerts
|

Depression in lung cancer patients: is the HADS an effective screening tool?

Abstract: The MADRS identified 92% of the patients as depressed; the HADS, 70% and 87%, using a cutoff of 11 and 8, respectively. The results suggest substantial agreement between the HADS and the MADRS when a cutoff of 8 is used (McNemar: p = 0.51; Cohen K = 0.69), while a HADS cutoff of 11 resulted in a significantly lower concordance with the MADRS (McNemar: p = 0.002; Cohen K = 0.49).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 19 publications
5
25
1
1
Order By: Relevance
“…To prevent families from an additional burden where a patient might have recently died or is in the palliative stage, we excluded tumor diagnoses with poor 5-year-survival rates such as lung cancer and brain tumors. Previous studies assessing anxiety and depression with the HADS found that lung cancer patients and advanced cancer patients reported higher rates of depression than in our sample [2, 4144]. Therefore, our study might underestimate anxiety and depression in working-age cancer survivors.…”
Section: Discussioncontrasting
confidence: 54%
“…To prevent families from an additional burden where a patient might have recently died or is in the palliative stage, we excluded tumor diagnoses with poor 5-year-survival rates such as lung cancer and brain tumors. Previous studies assessing anxiety and depression with the HADS found that lung cancer patients and advanced cancer patients reported higher rates of depression than in our sample [2, 4144]. Therefore, our study might underestimate anxiety and depression in working-age cancer survivors.…”
Section: Discussioncontrasting
confidence: 54%
“…Second, due to manpower considerations, depression was only assessed by a self-reported measure rather than formal diagnostic criteria. However, previous studies have demonstrated satisfactory sensitivity and specificity of the HADS, with a cutoff of eight, as a screening tool for depression in lung cancer patients [29]. Third, we did not include other psychological variables such as social support, coping style, or anxiety as the potential predictors for survival.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, three studies [14,35,39] had to be excluded from pooling because their prevalence rates were highly dissimilar from the majority of studies. A summary of all pooled findings is displayed in Table 2.…”
Section: Data Synthesismentioning
confidence: 99%